Estudo da audição e da auto-percepção do Handicap auditivo em motoristas de caminhão - Lopes, Gabriela (2007)
Introduction: Every society depends directly or indirectly on the road transport efficiency, which is mainly executed by truck drivers. On duty of this function, these professionals can show several health problems such as hearing impairment. Objective: This assignment has studied the hearing and the self-perception of the hearing handicap in truck drivers. Method: It was evaluated 75 truck drivers, male gender and ages between 27 to 61 years old, with professional experience between five to 40 years. It was accomplished: anamnesis, audiometric evaluation and also was applied a questionnaire, the Hearing Handicap Inventory for Adults (HHIA). Noise Induced Hearing Loss (NIHL) was classified according to the Group criterion used by Fiorini (1994). Audiometric evaluation also was classified according to Parrado-Moran, Fiorini (2003), taking into consideration the results for both ears separately. Results: 50 out of 75 (66.7%) have shown results within normal standards (Group 1), 20 out of 75 (26.7%) have been classified as suggestive of noise induced hearing loss (NIHL) (Group 2) and 5 out of 75 like the others (6.6%). Out of 50 Group 1 audiograms (71.4%), 31 were normal with bilateral notch (62.0%) and out of 20 Group 2 audiograms (28.6%), 16 (80.0%) were suggestive of bilateral NIHL. The greatest compromise was found in the frequency range of 4 kHz, 6 kHz and 8 kHz. Qualitative variables: years of duty profession (p=0.049) and age (p=0.049) have statistically influenced the audiometric evaluation results. Out of 50 truck drivers (71.4%) who presented normal hearing thresholds (Group 1), 43 subjects (86.0%) did not have a perceived hearing handicap, 6 (12.0%) had a mild/moderate perception and 1(2.0%) a severe/significant hearing handicap perception. Out of 20 truck drivers (28.6%) who presented suggestive NIHL (Group 2), 16 subjects (80.0%) did not show any degree of hearing handicap, 3 (15.0%) have presented it mild/moderate and one (5.0%) severe/significant. The largest compromise was found in the frequencies of 4 kHz, 6 kHz and 8 kHz. In relation to self-perception of the hearing handicap, 7 drivers (14%) from Group 1 and 4 (20.0%) from Group 2 have shown self-perception of the hearing handicap. However, 43 drivers (86.0%) of Group 1 and 16 (80.0%) of Group 2 did not show any perception. With this, it was noticed that not even all the drivers with suggestive NIHL showed a hearing handicap self-perception and those within normal hearing standards have presented it. Conclusion: The prevalence of hearing disorders on the analyzed population was 28.6%. Besides the years of duty profession and the age determined statistically the results of this audiometric evaluation and it did not have any connection with the results of the self-perceived hearing handicap